2022
DOI: 10.1002/cctc.202200060
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Mediated C−H Silylation of Aromatic Heterocycles with Hydrosilanes

Abstract: Treatment of mononuclear calcium hydride complex [(TpAd,iPr)Ca(H)(THP)] (1) (TpAd,iPr=hydrotris(3‐adamantyl‐5‐isopropyl‐pyrazolyl)borate, THP=tetrahydropyran) with 2‐methylthiophene, 2‐methylfuran, and 1‐methyl‐1H‐indole in THF/hexane solution led to the formation of calcium thiophenyl (2), furanyl (3), and indolyl (4) complexes, via sp2 C−H bond activation. The reaction of complex 1 with 2‐methylpyridine and quinoline afforded calcium benzyl pyridinyl (5) and 1,2‐dihydroquinolide (6) complexes, through sp3 C−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 102 publications
0
4
0
1
Order By: Relevance
“…他们分离 并表征了催化反应中间体茴香醚基钙配合物结构, 证明 底物烷氧基与钙中心的配位在该反应中起了重要作用, 并 根 据 动 力 学 研 究 绘 制 了 可 能 的 机 理 循 环 (Scheme 38B). 2022 年, 他们 [73] 还进一步将该催化体系拓展到杂 芳环的 α 位脱氢硅基化反应(Scheme 38C), 为合成含有 叔硅烷单元的(杂)芳基化合物提供了一种新的途径.…”
Section: 其他反应类型unclassified
“…他们分离 并表征了催化反应中间体茴香醚基钙配合物结构, 证明 底物烷氧基与钙中心的配位在该反应中起了重要作用, 并 根 据 动 力 学 研 究 绘 制 了 可 能 的 机 理 循 环 (Scheme 38B). 2022 年, 他们 [73] 还进一步将该催化体系拓展到杂 芳环的 α 位脱氢硅基化反应(Scheme 38C), 为合成含有 叔硅烷单元的(杂)芳基化合物提供了一种新的途径.…”
Section: 其他反应类型unclassified
“…This is because the reaction of Ca–H species with an unsaturated substrate has a high propensity to undergo hydride transfer rather than deprotonation . In recent years, Harder, Cheng, and our group have shown that molecular calcium hydrides/alkyls also enabled catalytic C–H alumination, silylation, and alkylation of a diverse array of substrates with high selectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Unwanted oxidation/reduction pathways typically with transition metals can be avoided as the metal oxidation state remains intact during the reaction. Due to the nontoxic, environmentally benign, earth-abundant, and biocompatible nature, calcium-based efficient catalysts have been actively pursued by many scientists as potential alternatives to expensive, toxic, and rare metal complexes. The hydrosilylation of hydrosilanes and olefins catalyzed by calcium complexes has been well studied during the past decade. ,, However, calcium-mediated catalytic bis-hydrosilylation of dienes through step-growth polyaddition to afford high-molecular-weight hydridopolycarbosilanes remains unreported, as far as we are aware. More recently, our group found that scorpionate-supported calcium benzyl complex [(Tp Ad, i Pr )­Ca­( p -CH 2 –C 6 H 4 -Me)­(THP)] (Tp Ad, i Pr = hydrotris­(3-adamantyl-5-isopropyl-pyrazolyl)­borate, THP = tetrahydropyran) ( 1 ) can serve as a powerful catalyst precursor for the catalytic hydrogenation of alkenes, ortho -regioselective dehydrogenative silylation of aromatic ethers, and aromatic heterocycles. , During these transformations, a mononuclear calcium hydrido complex was proposed as the key intermediate .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, our group found that scorpionate-supported calcium benzyl complex [(Tp Ad,iPr )Ca-(p-CH 2 −C 6 H 4 -Me)(THP)] (Tp Ad,iPr = hydrotris(3-adamantyl-5-isopropyl-pyrazolyl)borate, THP = tetrahydropyran) (1) can serve as a powerful catalyst precursor for the catalytic hydrogenation of alkenes, 56 ortho-regioselective dehydrogenative silylation of aromatic ethers, and aromatic heterocycles. 54,55 During these transformations, a mononuclear calcium hydrido complex was proposed as the key intermediate. 50 These findings have inspired our interest in the copolymerization of dienes and bis-hydrosilane by a calcium complex.…”
Section: ■ Introductionmentioning
confidence: 99%